Quality Management in China: Effects of Company Ownership and Size - Zhou, Jingxin (2011)
Purpose – The purpose of this dissertation is to discover the effect of company ownership and size on Chinese company’s QM development and their choices of QM initiatives, the effect of ISO 9000 series on other QM practices and the attitudes of the workers towards these initiatives. Design/methodology/approach – The research is entirely based on case studies in six Chinese manufacturing companies, covering all types of companies. Interviews are done with both the managers and workers in each company, and observations and documents are available in some of the cases. Findings – SOEs and foreign-owned companies have more progress compared with POEs, while larger companies are performing better in terms of Process control & continuous improvement, Education and training, Recognition and reward, and Supplier participation than the SMEs. For the choice of QM initiatives, SOEs prefer TQM and have made attempt for Six-Sigma, foreign-owned companies have developed their QM system based on their own experience and POEs are performing less inspiring. The company size is found to have no significant influence on this issue. The ISO 9000 series are found to have a facilitating effect to other QM practices as it provides the companies with a general framework to build the QM practices. When regarding worker’s attitudes, the majority of Chinese workers wish that financial incentives could be used to promote the QM practices. The empowerment and teamwork are receiving mixed feelings, as some workers have concerns about the associated extra workload and a tighter control from the managers. Research limitations/implications – The geographic concentration of the case companies and the small sample size for each type of the companies have brought the concern on the generality of the findings. Because of the author’s limited access to the companies, the interviews did not cover the top managers which are considered to be crucial to QM. Also, the effect of industry type is not tested in this dissertation. Practical implications – Chinese companies may consider using ISO 9000 series to build up the basis of QM system and develop based on their own experience. The company may also consider using TQM to educate the workers. In that case, Six-Sigma can be used to elevate the QM results. Financial incentives should be used to promote the practices. Keywords: TQM, Six-Sigma, IOS 9000 series, ownership, size, Chinese manufacturer.